Dietary Fructose and Glucose: The Multifacetted Aspects of Their Metabolism and Implication for Human Health (Vol. 1) - Luc Tappy (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
We welcome the submission of manuscripts, either describing original research, or reviewing scientific literature. Manuscripts should focus on well-defined topics, not previously reported extensively in the literature, such as (without being limited to): functional aspects of fructose and glucose metabolism health effects of chronic fructose and glucose consumption molecular and mechanistic insights of hexoses-induced metabolic adaptations sugars, sweet taste receptors and brain responses intervention studies in humans Papers covering species comparisons of nutrition/metabolism or evolutionary perspectives, or effects of fructose and glucose in specific physiological conditions (physical activity, pregnancy, growth, etc.) or special tissues (testis, placenta) are welcome.